Processing of wood plastic composites: The influence of feeding method and polymer melt flow rate on particle degradation. Issue 13 (10th December 2015) - Teuber, Laura; Militz, Holger; Krause, Andreas
ABSTRACT: Spruce wood particle (WP)/polypropylene (PP) compounds were prepared in an internal mixer using different rotor speeds. To analyze the effect of feeding method on particle degradation, WP and PP were either fed as dry‐blend or WP was fed into the PP melt. To prevent melt freezing, pre‐heated WP were used as comparison to cold WP. In addition, WPs were compounded with different grades of PP or high‐density polyethylene (HDPE) to analyze the effect of polymer matrix melt flow rate (MFR) on particle degradation. Mixing behavior of compounds containing 30% and 70% (w/w) WP depended on feeding method, represented by a changing relation of final torque values. Feeding as dry‐blend and using pre‐heated particles led to stronger WP degradation. Degradation decreased with increasing polymer MFR. For PP compounds, particle degradation was stronger when containing 70% WP, for HDPE the difference due to WP content was only marginal. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43231. Abstract :